PENGARUH BAURAN PEMASARAN DIGITAL TERHADAP MINAT BELI KONSUMEN PADA PEMBELIAN TIKET KERETA API ONLINE MELALUI APLIKASI DI KABUPATEN TULUNGAGUNG - Mustika Nur Astuti; Muhammad Aswad (AmaNU: Jurnal Manajemen dan Ekonomi, 2022)
The purpose of this study was to determine the effect of the digital marketing mix on consumer buying interest partially or simultaneously, and to identify the most dominant marketing mix variable on consumer buying interest in purchasing train tickets online through applications in Tulungagung Regency. This study uses a descriptive quantitative approach, where the sampling technique uses purposive sampling method. The data collection process was carried out by distributing questionnaires at least once to users of the KAI Access application in Tulungagung Regency. The research data were tested with validation tests, reliability tests, descriptive statistical tests, classical assumption tests, and hypothesis testing. With the help of SPSS 21, multiple linear regression analysis was used to analyze the data in this study. Partially, there are five variables that influence, namely price, place, people, process, and physical evidence, and two variables that have no effect, namely product and promotion. The digital marketing mix has a significant effect on consumer buying interest in the amount of 91.6%, and the remaining 8.4% is influenced by other variables not included in this survey. The digital marketing mix variable that is very dominant or often influences consumer buying interest is the process variable. Taken from the value of t arithmetic which has the largest value among other variables.